2010
DOI: 10.1177/1534735410385112
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Deleterious Effects of DMBA-Induced Skin Carcinogenesis in Mice by Syzygium cumini Seed Extract

Abstract: The inhibition of tumor incidence by hydro-alcoholic extract of S.cumini seed was evaluated in mice on two stage process of skin carcinogenesis induced by single application of 7, 12-dimethyl benz(a)anthracene (100 µg/100µl of acetone), and 2 weeks later promoted by repeated application of croton oil (1% acetone/thrice in a week) till the end of the experiment (i.e. 16 weeks). Oral administration of extract at a dose of 250mg/kg b.wt./day at the peri-initiational stage (i.e. 7 days before and 7 days after DMBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…The hydroethanolic extract of the seed prevented the DMBA-induced croton oil promoted skin (Parmar, Sharma, Verma and Goyal, 2010;Parmar, Sharma, Verma, Sharma, et al, 2010b) and benzo a pyrene-induced gastric carcinogenesis in mice (Goyal et al, 2010).…”
Section: Chemopreventive Effectsmentioning
confidence: 96%
See 2 more Smart Citations
“…The hydroethanolic extract of the seed prevented the DMBA-induced croton oil promoted skin (Parmar, Sharma, Verma and Goyal, 2010;Parmar, Sharma, Verma, Sharma, et al, 2010b) and benzo a pyrene-induced gastric carcinogenesis in mice (Goyal et al, 2010).…”
Section: Chemopreventive Effectsmentioning
confidence: 96%
“…Recently, Parmar, Sharma, Verma and Goyal (2010); Parmar, Sharma, Verma, Sharma, et al (2010b) have reported that jamun possess cancer chemopreventive properties in the DMBA-induced croton oil promoted two stage skin carcinogenesis in Swiss albino mice. Feeding 125 and 250 mg/kg/b.…”
Section: Chemopreventive Effectsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results suggest a possible chemopreventive property of S.cumini against DMBA induced skin carcinogenesis in mice 16 .…”
Section: Syzygium Cumini Linn Skeelsmentioning
confidence: 87%
“…There are various medicinal plants which have significant medicinal values and are widely used in folklore medicine. The literature reveals that flavonoids, alkaloids, terpenes of plant derived products have received considerable attention in recent years due to their diverse pharmacological properties including cytotoxicity and cancer chemopreventive effects 3 .…”
Section: Introductionmentioning
confidence: 99%